Utilization of LDPE plastic bag wastes into building blocks / Raja Iman Nadiah Raja Sahrul Hishan - Raja Sahrul Hishan, Raja Iman Nadiah (2019)
Plastic material is one of the biggest usages in the worldwide especially Low-Density Polyethylene (LDPE) types. The most common used of plastic material is LDPE plastic bags that being used for many applications. The wastes that were generated from the LDPE plastic bags became a great concern towards the whole world as it made with material that difficult to decompose. Besides, with the increment in application with LDPE plastic bags, the environmental pollution also increases and might affect the health of other people. This study is mainly to utilize the LDPE plastic bags into other useful products which is building block. With the replacement of certain proportions of raw materials with LDPE plastic bags materials can help to increase the quality of the blocks. The modified blocks were made from mixtures of some proportions of LDPE plastic bag, proportions of cement, fine sand and hardener. This study was mainly to test the quality of the modified block and the effect of replacement of plastic material to the properties of the block by conducting compressive strength test, water absorption test, heavy metal analysis and Fourier Transform Infrared Spectroscopy (FTIR) analysis. The test was conducted on five different sample with different proportions of plastic material and cement.